Annual review of information technology developments for economic and social historians, 1994. - Middleton, Roger (Economic History Review, 1995)
The writer presents a summary overview of recent developments in information technology for economic and social historians, together with a detailed comparative review of a major class of applications software: text base management systems (TBMS). The writer explains that TBMS ranges from text retrieval to text processing and analysis, and he contends that the explosion in the volume of machine-readable materials now available is so large that British economic historians all require TBMS.